Rate' Singing: Religious humming as a marker of cultural identity in Makassar’s life cycle rituals - Khaeruddin, Khaeruddin; Rachmat, Rachmat (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
This research on traditional arts related to religion or belief aims to uncover the life cycle flow of the Makassarese people through Rate's singing. The specific objectives of this research are to answer the following questions: (1) What is the function of Rate' singing? (2) Why is Rate's singing currently rarely performed in Makassar ethnic communities? (3) How can the regeneration of Rate's singing be achieved? This ethnographic qualitative research employs various data collection methods, including observation, interviews, and document studies. The research was conducted in Makassar and Gowa cities. The results indicate the following: (1) The function of Rate' in the Makassarese community is primarily as a medium for prayer, an invitation for good fortune, a rejection of bad luck, a confirmation of customary procedures, and a means of ethical education for the next generation. Rate' singing in sacred Makassarese activities aims to bring people closer to God; (2) The period of turmoil in Sulawesi, starting with the arrival of Japan and followed by the struggle for Indonesian independence, influenced the continuity of traditional art in South Sulawesi, particularly Makassarese art. After the security in South Sulawesi gradually recovered, the community began to focus on improving their welfare, viewing cultural arts, especially traditional ceremonies, as wasteful and non-materially beneficial; (3) Rate' singing faced near extinction as the nobility, or karaeng descendants, began to lose their traditional culture. The remaining Pa'Rate' are few and elderly, with no successors to inherit their knowledge. As a form of literature, the traditional way of conveying Rate' is known only to older generations. The transmission of ma'Rate's skills is conducted within the Parate family itself.